2021
DOI: 10.3389/fpsyg.2021.612317
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Subjective/Objective Status and Possible Pathways of Young Migrants’ Life Satisfaction and Psychological Distress in China

Abstract: Young migrants have been the major migrant labor force in urban China. But they may be more vulnerable in quality of life and mental health than other groups, due to their personal characteristic and some social/community policies or management measures. It highlights the need to focus on psychological wellbeing and probe driving and reinforcing factors that influence their mental health. This study aimed to investigate the influence of subjective/objective status and possible pathways of young migrants’ life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 112 publications
1
13
0
Order By: Relevance
“…The SSS measures keep their predictive power after controlling for objective measures (e.g., income poverty or household income) and are mostly stronger predictors of PD (Chang et al, 2020; Chung et al, 2018; Sakurai et al, 2010). Although several studies on young adults have documented the socioeconomic gradient in mental health using objective SES measures (e.g., von Soest et al, 2012), there is limited empirical evidence on the SSS-PD association among young adults (Achdut et al, 2021) and most studies in this area are based on samples of students (Dyrbye et al, 2006; Reyes & Yujuico, 2014; Saïas et al, 2014; Schubert et al, 2016; Vázquez et al, 2012; Vidal et al, 2018) or immigrants (Chiang et al, 2021). These groups cannot adequately represent young adults in general—especially when considering SES and other social stressors.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…The SSS measures keep their predictive power after controlling for objective measures (e.g., income poverty or household income) and are mostly stronger predictors of PD (Chang et al, 2020; Chung et al, 2018; Sakurai et al, 2010). Although several studies on young adults have documented the socioeconomic gradient in mental health using objective SES measures (e.g., von Soest et al, 2012), there is limited empirical evidence on the SSS-PD association among young adults (Achdut et al, 2021) and most studies in this area are based on samples of students (Dyrbye et al, 2006; Reyes & Yujuico, 2014; Saïas et al, 2014; Schubert et al, 2016; Vázquez et al, 2012; Vidal et al, 2018) or immigrants (Chiang et al, 2021). These groups cannot adequately represent young adults in general—especially when considering SES and other social stressors.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…In terms of acculturation, as revealed in the acculturation theory, the life changes that trigger acculturation are sometimes beneficial and offer new development opportunities to the acculturated person, but sometimes they bring about a great deal of pressure, which has a pronounced effect on the health of migrating or floating populations ( Fox et al, 2017 ). In terms of social adaptation, young migrants have lost their original interpersonal networks, but the construction of new social networks and social interactions can lower the negative impact that social adaptation produces on their mental health and improve their social position and development of social functions ( Chiang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Individual socioeconomic characteristic such as age, occupation, income and longer time in the host cities could determine sense of belonging [17,18]. Some researchers have suggested that migrants with greater social adaptation skills, language skills, interpersonal skills, connections with local residents, degrees of acceptance, and roles consciousness may exhibit a higher sense of city belonging and identity [19][20][21][22][23]. With respect to individual psychological feelings, some scholars indicated that life satisfaction was positively and directly correlated to immigrants' sense of belonging [24].…”
Section: Influencing Factors Of Sense Of City Belongingmentioning
confidence: 99%